The accuracy and precision of insulin administration using human and veterinary pen‐injectors and syringes for administration of insulin. (15th May 2021) - Malerba, Eleonora; Fracassi, Federico; Del Baldo, Francesca; Golinelli, Stefania; Ceccherini, Martina; Barbarossa, Andrea
Abstract: Background: Many diabetic dogs and cats require small doses of insulin that must be administered accurately. Objectives: To compare the accuracy and precision of insulin syringes and pen‐injectors. Animals: None. Methods: To determine how accurately and precisely insulin doses are delivered, 0.5, 1, 2, 4, 8, and 16 U doses were dispensed 25 times from 5 SoloSTARs, 5 FlexPens, 5 KwikPens, 5 JuniorSTARs, 5 VetPens 0.5‐8 U, 5 VetPens 1‐16 U, and by 5 veterinarians using 30 U/0.3 mL and 40 U/mL insulin syringes. Each dose was weighed, using a precision balance, and the intended and delivered doses were compared. Results: All pen‐injectors delivered less insulin than the intended dose, underdosage being inversely proportional to insulin dose. The differences between the intended and the delivered dose were not significant using JuniorSTAR and VetPen 0.5‐8 U at insulin doses of 0.5, 1, 2, and 4 U, using the 30 U/0.3 mL insulin syringe at the 4 U dose and using the 40 U/mL insulin syringe at the 4, 8, and 16 U doses. With all the devices, precision increased with increasing doses of insulin. The coefficient of variation was <8% for all 6 pen‐injectors. Conversely, using 30 U/0.3 mL and 40 U/mL syringes at an insulin dosage of 0.5 U the coefficients of variation were 12.08% and 9.39%, respectively. Conclusions and Clinical Importance: JuniorSTAR and VetPen 0.5‐8 U were more accurate than the other devices when delivering ≤2 U doses, while the delivery of 8 and 16 U doses was more accurate using 40 U/mL syringes.